ANALISIS KUALITAS SABUN PENCUCI TANGAN CAIR DARI EKSTRAK DAUN KEMANGI (Ocymum basilicum L.) SEBAGAI ANTIBAKTERI ALAMI - Melantina Oktriyanti; Erika Dwi Oktaviani; Nina Hartati; Sofiah Sofiah; Shella Dwitasari (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
Hand soap is one of the means to clean hands from dirt, germs and other things that make hands dirty. To kill bacteria, some hand soaps contain active substances that can have a negative effect on humans who have sensitive skin, which can cause irritation. Some synthetic active ingredients that are harmful to human skin health are diethanolamine (DEA), Sodium Lauryl Sulfate (SLS), and triclosan which functions as an antibacterial. This study aims to obtain the composition of basil leaf extract with the right maceration time as an antibacterial and can produce liquid hand soap products that are in accordance with the quality of SNI 2588:2017 by varying the composition of the basil leaf extract and varying the maceration time. Variations in the composition of basil leaf extract are 3%, 6%, and 9% as well as variations in maceration time of 3 days and 7 days. Analysis of liquid hand soap products includes pH, insoluble in ethanol, free fatty acid content, surface tension, organoleptics, and bacteria. Based on the results of the analysis, all samples met the quality of SNI, but the sample with the best formulation of liquid hand soap was obtained at a composition of 9% extract (9 ml of basil leaf extract in 100 ml of soap volume) with a maceration time of 7 days. The results of the analysis showed that the resulting pH value is 8, the material is insoluble in ethanol 0.46%, free fatty acids 0.32% and the surface tension of soap is 13.52 dyne/cm.